Analisis RIsiko Keamanan Teknologi Infromasi Pada Instansi Pemerintahan Purbalingga - Aprilia, Kharisma; Maghfira, Rahajeng Sasi; Aji, Ranggi Praharaningtyas; Saputra, Dhanar Intan Surya (Journal of Practical Computer Science, 2025)
Digital transformation within the governmental sector has accelerated the wide use of information systems for the support of public services and administrative efficiency. However, this development has also introduced serious challenges of information security that are often overlooked by local governments. The purpose of this research is to identify and assess the risk of IT security at Kabupaten Purbalingga’s Department of Communication and Information . The research is to be conducted using the qualitative descriptive approach based on the OCTAVE-S method. Data collection will involve direct observation of IT infrastructure and a thorough interview with the technical personnel responsible for information systems. From the analysis conducted, it can be concluded that DINKOMINFO has serious threats such as defacement attacks, DDoS, and internal vulnerabilities due to the use of weak credentials. Without a strong security policy, these weaknesses will only become more widespread, not much different from the current resource limitations. Therefore, the best solution that can be implemented in the long term is the implementation of a Security Operation Center or SOC, adaptive security policies, and cybersecurity awareness and training. Keyword: Information Security, OCTAVE-S, Local Government, DINKOMINFO, Cyber ​​Risk.